1970
DOI: 10.1002/star.19700220204
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Dextrinization. Part I. Pyrodextrinization of Corn Starch in the Absence of Any Added Catalyst

Abstract: Corn starch has been dextrinized at a bath temperature of 121 '-213 OC. In certain cases, the moisture content o f the starch was reduced to 2010 before it was subjected to dextrinization. Under the various conditions of dextrinization, the changes that take place in the properties of starch such as solubility, reducing power, alkali lability, intrinsic viscosity and B-amylolysis have been recorded. These results show that at lower temperatures o f 121 O and 110 O C hardly any reaction is perceptible, the dext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The star& (H,O 6 o/o, 70 g) was roasted in a glass flask a t various times and temperatures (see Table 1). [4,9,101. Dextrin ( 5 g) was immersed in ethanol (4 ml), and then diluted with water to 100 ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The star& (H,O 6 o/o, 70 g) was roasted in a glass flask a t various times and temperatures (see Table 1). [4,9,101. Dextrin ( 5 g) was immersed in ethanol (4 ml), and then diluted with water to 100 ml.…”
Section: Methodsmentioning
confidence: 99%
“…At higher temperature, the shortened units are repolymerized and the degree of branching increases considerably. More recently, Greenwood [ 11, Srivastava [9], Kainuma [lo], and several workers [2,11,121 studied dextrinization and reported many interesting results.…”
Section: Studies On Pyrodextrinization Of Corn Starchmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reported that extrusion cooking resulted in the transformation of native starches into lower molecular weight fragments, and that fragmentation was a function of extrusion conditions and possibly, starch source. Greenwood (1967) and Srivastava et al (1970) suggested that starch, when subjected to high temperatures (125 to 213ЊC), underwent covalent reassociation. This was not confirmed by Wen et al (1990) or Wasserman and Tampa (1991).…”
Section: Introductionmentioning
confidence: 99%